Building materials, materials design and applications : selected, peer reviewed papers from the 4th International Conference on Building Materials and Construction (ICBMC 2019), February 25-28, 2019, Singapore and the 2nd International Conference on Materials Design and Applications (ICMDA 2019), April 13-15, 2019, Tokyo Japan - Sun, Hongqi, 1962-; Omatsu, Takashige; Yang, Tracy (Trans Tech Publications Ltd, 2019)
This volume contains a selection of papers submitted to the 4th International Conference on Building Materials and Construction (ICBMC 2019, February 25-28, 2019, Singapore) and the 2nd International Conference on Materials Design and Applications (ICMDA 2019, April 13-15, 2019, Tokyo, Japan). The conference proceedings present recent advances in the field of building materials, concrete structures, ductility, crack resistance, fatigue, fracture mechanics, materials properties and technologies of materials processing. Concrete, Mortar, Reinforcing, Concrete Structure, Fracture, Mechanical Properties, Polymers, Composites, Nanomaterials, Membrane, Thin Films, Welding, Plasma Treatment, Thermal Spray Coating, Machining Materials Science, Building Materials, Mechanical Engineering.
Keywords: Building materials -- Congresses.; Structural engineering -- Congresses.; elektronické knihy; electronic books